Hubungan tingkat pengetahuan kanker serviks dengan minat vaksinasi HPV pada mahasiswi Fakultas Ekonomi Universitas Palangka Raya - I Gde Hary Eka Adnyana; Angeline Novia Toemon; I Wayan Bayu Satyaguna Wibawa (Barigas: Jurnal Riset Mahasiswa, 2023)
Cervical cancer first ranks in developing countries and is the top ten most common diseases in developed countries. Cervical cancer is 2 out of the 10 most common cancers in Indonesia with an incidence of 12.70%. Indonesia has a population of 99.8 million women aged 15 years and over who are at risk of developing cervical cancer. The purpose of this study was to find out the relationship between the level of knowledge of 2019 Faculty of Economics students regarding cervical cancer and interest in HPV vaccination. The method used is analytic observational with cross-sectional design. The population in this study used a purposive sampling technique where the samples were female students aged over 18-25 years at the Faculty of Economics years of 2019 with a total sample of 100 samples. Data collection was carried out using primary data through validated questionnaires, after which a chi-square test was carried out. and computerized data processing. The results of this study indicate that there is a significant relationship between the level of knowledge of cervical cancer (p-value = 0.000) and interest in HPV vaccination.